The Effect of Perceived Organizational Support and Transformational Leadership on Employee Performance (Study on Manufactuning Companies in Cirebon) - Ramadhana Farel Laisya Nazay; Astri Leviyani; Budi Agung Prasetya (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to conduct an analysis of the effect of Perceived Organizational Support (POS) and Transformational Leadership on employee performance in manufacturing companies in Cirebon City. POS is related to how far employees assess that the organization values employee involvement and is concerned about their welfare, while transformational leadership focuses on how leaders inspire and motivate employees to achieve optimal results. This study uses a quantitative approach through multiple linear regression analysis. Data was collected from 105 respondents through questionnaires. The results show that POS has no significant influence on employee performance, indicating the need to evaluate the form of organizational support to be more relevant to employee needs. In contrast, transformational leadership has a significant influence on employee performance, confirming the importance of the leader's role in forming an inspiring and supportive work environment. Simultaneously, these two variables contribute 58.1% to employee performance, while 41.9% is influenced by other factors. The findings provide practical implications for companies in increasing leadership effectiveness and improving organizational support strategies to improve employee performance. Further research is recommended to explore other factors, such as organizational culture and work-life balance, that may affect employee performance.